An Amphipathic Alpha‐Helix Guides Maturation of the Ribosomally‐Synthesized Lipolanthines. Issue 38 (24th July 2020) - Wiebach, Vincent; Mainz, Andi; Schnegotzki, Romina; Siegert, Mary‐Ann J.; Hügelland, Manuela; Pliszka, Nicole; Süssmuth, Roderich D.
Abstract: The recently discovered strongly anti‐Gram‐positive lipolanthines represent a new group of lipidated, ribosomally synthesized and post‐translationally modified peptides (RiPPs). They are bicyclic octapeptides with a central quaternary carbon atom (avionin), which is installed through the cooperative action of the class‐III lanthipeptide synthetase MicKC and the cysteine decarboxylase MicD. Genome mining efforts indicate a widespread distribution and unprecedented biosynthetic diversity of lipolanthine gene clusters, combining elements of RiPPs, polyketide and non‐ribosomal peptide biosynthesis. Utilizing NMR spectroscopy, we show that a (θxx)θxxθxxθ (θ=L, I, V, M or T) motif, which is conserved in the leader peptides of all class‐III and ‐IV lanthipeptides, forms an amphipathic α‐helix in MicA that destines the peptide substrate for enzymatic processing. Our results provide general rules of substrate recruitment and enzymatic regulation during lipolanthine maturation. These insights will facilitate future efforts to rationally design new lanthipeptide scaffolds with antibacterial potency. Abstract : Twist and modify ! Enzymatic and structural investigation of the lipolanthine biosynthesis revealed the leader peptide of microvionin to form an amphipathic α‐helix, containing a highly conserved, hydrophobic (θxx)θxxθxxθ motif essential for enzymatic modification and subsequent proteolytic degradation. Efficient processing is additionally dependent on mutual regulation between the corresponding maturation enzymes.